The Cambridge history of Scandinavia (Cambridge University Press, 2003)
The various countries and communities that constitute present-day Scandinavia consider themselves as integral parts of that larger region. Denmark, Norway, Sweden, Finland, Iceland, and Greenland share a common geographic, historic and socio-cultural distinctness that differs from the rest of Europe. This "distinctness" provides the rationale for compiling a comprehensive and comparative history of Scandinavia